2015
DOI: 10.2967/jnumed.114.145177
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Dosimetry with Intensification Using 90Y-Loaded Glass Microsphere Radioembolization Induces Prolonged Overall Survival in Hepatocellular Carcinoma Patients with Portal Vein Thrombosis

Abstract: The objective of this study was to evaluate the response rate and survival of hepatocellular carcinoma portal vein thrombosis (PVT) patients treated with 90 Y-loaded glass microspheres using a personalized dosimetry and intensification concept. Methods: The microspheres were administered to 41 hepatocellular carcinoma PVT patients (main 5 12; lobar/segmental 5 29). 99m Tc-macroaggregated albumin SPECT/CT quantitative analysis was used to calculate the tumor dose (TD), healthy injected liver dose (HILD), and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
103
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 22 publications
5
103
0
4
Order By: Relevance
“…However, radioembolization has a low embolic effect, and most of the arterial tree remains patent after treatment (6,7). Radioembolization in the setting of PVT is therefore safe and can sometimes lead to complete portal vein revascularization, even in main PVT (8). In contrast to transarterial chemoembolization (TACE), PVT is not considered a contraindication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, radioembolization has a low embolic effect, and most of the arterial tree remains patent after treatment (6,7). Radioembolization in the setting of PVT is therefore safe and can sometimes lead to complete portal vein revascularization, even in main PVT (8). In contrast to transarterial chemoembolization (TACE), PVT is not considered a contraindication.…”
mentioning
confidence: 99%
“…In contrast to transarterial chemoembolization (TACE), PVT is not considered a contraindication. Radioembolization is an emerging indication in early-advanced hepatocellular carcinoma (HCC) (Barcelona Clinical Liver Cancer [BCLC] C, liver-dominant, Eastern Cooperative Oncology Group [ECOG] 1-2, PVT) (8). On the basis of current evidence, application of radioembolization in patients with a ChildPugh score higher than B7 and main PVT should be weighed carefully, because of the limited potential survival benefit after radioembolization (4.5-5 mo in Child-Pugh B patients and 2.5 mo in Child-Pugh C patients vs. 2.7-4.0 mo in untreated patients) (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…In these patients, PET/CT demonstrated that microspheres distributed within the PVT (24). Overall survival of these patients improved using the boosted personalized dose method described by Garin et al in which the tumor dose of 205 Gy was achieved through increasing the lobar dose to a 150-Gy maximum (25). From our study, the perfused volume would include both the right and the left lobar volumes for 62.5% of the patients with HCC and PVT.…”
Section: Figurementioning
confidence: 92%
“…Secondly, a more personalized oncological approach is believed to potentially yield superior clinical results. This last point certainly appears to be true when using MAA SPECT/CT dosimetry and intensification for PVT patients, with an OS rate reaching 20 months for good candidates [15]. Lastly, the availability of this predictive factor of response and survival prior to therapy initiation is a clear advantage for radioembolization, as this is not the case with other therapeutic approaches used for liver cancer, such as chemotherapy, targeted therapies or chemoembolization.…”
mentioning
confidence: 99%
“…This point is of particular significance for three main reasons. First of all, given that MAA dosimetry is available prior to therapy initiation, it can lead to a fully personalized approach with a better selection of responders, improved identification of patients at risk of liver failure, and can even be used for treatment intensification, as recently suggested [11,15]. Secondly, a more personalized oncological approach is believed to potentially yield superior clinical results.…”
mentioning
confidence: 99%